Influence of a Retarding Admixture on the Behavior of Mortars Made from Different Types of Cement - Merawi Borhan, Tumadhir; A. Al-Ramahee, Munaf; Al-Hassnawi, Noor; Ali AlZaidi, Zaid (International Journal of Engineering and Technology, 2018)
The effect of retarding admixture on the fresh and hardened behaviour of different types of cement mortars and pastes when using a retarding admixture was investigated in this study. The types of cement used are; White cement (WhC), Ordinary Portland cement (OPC) and Sulphate Resistant Portland cement (SRC). Different cement mortar and paste mixes were cast, for this purpose, with and without the admixture. Initial and final setting times, compressive strength, length change, absorption and density for these mixes were examined at the curing ages of 3,7,28,45 days. The results showed that the addition of retarding admixture delayed the setting time significantly of WhC paste. The retarding admixture has a positive effect on the compressive strength of the mortar specimens for all types of cement used. regarding the length change test, the admixture was found to reduce the initial expansion for all types of cement at all ages. The results also showed an increase in the density and decrease in water absorption, especially at the later ages for all types of cement.  Among all cement types used, WhC was noticeably the most affected type by using the retarding admixture compared to other types of cement used.
Keywords: Cement type; Compressive strength; length change; Retarding admixture; Setting time.